Block periodization versus traditional training theory: a review - Issurin, V. G. (The Journal of Sports Medicine and Physical Fitness, 2008)
The basis of contemporary training theory were founded a few decades ago when knowledge was far from complete and workload levels, athletic results and demands were much lower than now. Traditional training periodization, i.e. the division of the seasonal program into smaller periods and training cycles, was proposed at that time and became a universal and monopolistic approach to training planning and analysis. Further sport progress emphasized the limitations and drawbacks of traditional periodization with regard to the preparation of contemporary top-level athletes and their demands. Major contradictions between traditional theory and practice needs appeared as 1) an inability to provide multi peak performances during the season; 2) the drawbacks of long lasting mixed training programs; 3) negative interactions of non-compatible workloads that induced conflicting training responses; and 4) insufficient training stimuli to help highly qualified athletes to progress, as a result of mixed training. The trials and successful experiences of prominent coaches and researchers led to alternative training concepts and, ultimately, to a reformed training approach that was called block periodization (BP). Its general idea suggests the use and sequencing of specialized mesocycle-blocks, where highly concentrated training workloads are focused on a minimal number of motor and technical abilities. Unlike traditional periodization, which usually tries to develop many abilities simultaneously, the block concept suggests consecutive training stimulation of carefully selected fitness components. The rational sequencing of specialized mesocycle-blocks presupposes the exploitation and superimposition of residual training effects, an idea that has recently been conceptualized and studied. It is hypothesized that different types of mesocycle-blocks are suitable to various modes of biological adaptation, i.e. homeostatic regulation or a mechanism of general adaptation.